2021
DOI: 10.3390/jtaer16070179
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality Traits on Choice of Retail Purchasing Channel: Literature Review and Research Agenda

Abstract: Consumers can choose to buy products through various retail channels (e.g., online or in-store), resulting in a need for retailers to provide a well-integrated shopping experience. However, individual factors, such as a customer’s personality, can influence how a channel is perceived and, as such, can alter their subsequent behavior. Thus, it is critical for retailers to better understand personality-related influences and how these can affect a customer’s purchase channel decision. Against this background, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…Furthermore, some researchers, such as Piroth et al (2020a) and Lixăndroiu et al (2021) , have found no direct relationships at all between Big Five traits and online shopping behavior ( Piroth et al (2020a) considered attitudes toward the adoption of online grocery shopping; and Lixăndroiu et al (2021) researched online buying intentions). As for in-store shopping, prior research has shown that Big Five traits can affect related motivations, but studies on the relations of Big Five traits with willingness to purchase in-store remain scarce ( Hermes and Riedl, 2021b ). Finally, despite the recent trend toward omnichannel retailing, the majority of published research has considered either online shopping or in-store shopping, but not both ( Hermes and Riedl, 2021b ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, some researchers, such as Piroth et al (2020a) and Lixăndroiu et al (2021) , have found no direct relationships at all between Big Five traits and online shopping behavior ( Piroth et al (2020a) considered attitudes toward the adoption of online grocery shopping; and Lixăndroiu et al (2021) researched online buying intentions). As for in-store shopping, prior research has shown that Big Five traits can affect related motivations, but studies on the relations of Big Five traits with willingness to purchase in-store remain scarce ( Hermes and Riedl, 2021b ). Finally, despite the recent trend toward omnichannel retailing, the majority of published research has considered either online shopping or in-store shopping, but not both ( Hermes and Riedl, 2021b ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As for in-store shopping, prior research has shown that Big Five traits can affect related motivations, but studies on the relations of Big Five traits with willingness to purchase in-store remain scarce ( Hermes and Riedl, 2021b ). Finally, despite the recent trend toward omnichannel retailing, the majority of published research has considered either online shopping or in-store shopping, but not both ( Hermes and Riedl, 2021b ). Thus, we add to the literature by exploring the effects of all Big Five traits on in-store and online willingness to purchase, and we expected the following:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering clients' personality traits can help make the e-commerce experience more personalized than before and increase overall customer satisfaction. A. Hermes's study shows what types of customers are likely/unlikely to shop online and how personality-based interests affect the purchasing channel choice [5]. A customer behavior-based recommendation system that utilizes statistical methods and dynamic user preferences analysis shows improvements in performance metrics (F-function score, precision, recall, and root mean square error) and overall prediction results.…”
mentioning
confidence: 99%